Development of Islamic Religious Education and Ethics Teaching Module for Class X of High School: An Approach Based on Islamic Values and the Independent Curriculum - Tasbi, Hasniar; Ilham, Dodi; Arifuddin, Arifuddin (Educational Journal of Learning Technology, 2025)
This research aims to develop a teaching module for Islamic Religious Education and Ethics for class X at SMA Negeri 1 Palopo using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments include interviews, documentation, and assessment sheets (questionnaires). The results of the study show that the teaching module received validation from media experts of 70.83% (valid), material experts of 89.58% (very valid), and linguists of 67% (valid). The practicality test from the teacher gave a result of 75% (practical). Thus, this teaching module is considered valid and practical to be used as an effective learning medium in Islamic Religious Education and Ethics subjects.